Nitrogen and phosphorus non-point source pollution in the upper Wujiang River Karst Basin: Critical source areas identification and influencing factors - Chengcheng Hu; Qixin Wu; Guodong Liu; Haiyan Ran; Mingzhe Guo; Jianping Zhu; Jie Zeng (Ecological Indicators)
Non-point source (NPS) pollution poses a severe threat to the safety of aquatic environments. The self-cleaning ability of karst systems can effectively reduce the level of NPS pollution. However, affected by high-intensity rainfall and agricultural NPS pollution, the water quality deteriorated during a special period. In this study, based on the field sampling and process of nitrogen and phosphorus nutrient loss simulated by the Soil and Water Assessment Tool (SWAT), to evaluate water quality and NPS pollution of typical karst basins in the upper Wujiang River. The results of the water quality assessment indicated that the Baifu River was relatively poor. According to the SWAT model, the critical source areas of NPS pollution were located in areas with a significant proportion of cultivated land in the midstream of the basin. The analysis of influencing factors reveals that in the southwest plateau region, sloping agricultural land significantly affects NPS pollution in karst rivers, especially cultivated land with slopes ranging from 11° to 25°. Sloping agricultural land increases soil erosion, leading to intensified nitrogen and phosphorus loss. This study contributes to the effective and targeted management of NPS pollution in basins with a high proportion of sloping agricultural land in karst regions.